NIELSEN THEORY AND SOME SELECTED APPLICATIONS TO DIFFERENTIAL AND INTEGRAL EQUATIONS; A BRIEF SURVEY - Khamsemanan, N. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we first give a quick introduction to Nielsen theory in the traditional topological setting. We then turn to the applications of Nielsen theory and survey some results in nonlinear analysis.